PENGARUH ELECTRONIC WORD OF MOUTH DAN PERSEPSI HARGA TERHADAP KEPUTUSAN PEMBELIAN DENGAN CITRA MEREK SEBAGAI VARIABEL MEDIASI PRODUK SKINTIFIC DI TIKTOK PADA GENERASI Z - Kayyisah Aulia Rahman; Dita Puruwita; Sefrimel Angriani ZN (STKIP Subang, 2026)
This study aims to analyze the influence of Electronic Word of Mouth (e-WOM) and Price Perception on Purchase Decision of Skintific products on TikTok among Generation Z, both directly and through Brand Image as a mediating variable. This study used a quantitative approach with a survey method. The population consisted of TikTok users who had purchased Skintific products, with a sample of 170 respondents aged 18–24 domiciled in DKI Jakarta, selected through non-probability sampling with a purposive sampling technique. Data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with the assistance of SmartPLS software. The results show that Electronic Word of Mouth, Price Perception, and Brand Image each have a positive and significant effect on Purchase Decision. In addition, Electronic Word of Mouth and Price Perception also have a positive and significant effect on Brand Image. The mediation test results indicate that Brand Image positively and significantly mediates the effect of Electronic Word of Mouth and Price Perception on Purchase Decision. These findings confirm that, alongside strengthening digital communication and pricing strategies, reinforcing Brand Image is an important mechanism for driving Purchase Decisions of skincare products on TikTok among Generation Z.